Теоретичні і практичні проблеми організації та діяльності Уповноваженого Верховної Ради з прав людини - Словська, Ірина Євгенівна; Словская, Ирина Евгеньевна; Slovskaja, Irina (My University, 2012)
The article is devoted to the comprehensive research that examines the legal nature of the institute of ombudsman: functions and its place in the system of state authorities, order of formation and forms of activity. Ñontains concrete suggestions towards further improvement of the legal basis of Human Rights Commissioner of Supreme Soviet of Ukraine status aiming at strengthening the effectiveness of his control, supervision and law-protection activites.
Словська І. Є. Теоретичні і практичні проблеми організації та діяльності Уповноваженого Верховної Ради з прав людини / І. Є. Словська // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2012. – Т. 11. – С. 85-91.
Keywords: омбудсман; Уповноважений Верховної Ради України з прав людини; порушення прав людини; забезпечення прав людини; Уполномоченный Верховной Рады по правам человека; нарушение прав человека; обеспечение прав человека; ombudsman; Human Rights Commissioner of Supreme Soviet of Ukraine; violation of human rights; human rights protection